Knowledge and Attitudes of the Younger Generation towards Money Politics in the 2024 General Election - Hertanto, Hertanto; Mulyaningsih, Handi (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The purpose of this study is to explain and analyze the knowledge and attitudes of the younger generation towards money politics in the general election campaign in Lampung in 2024. This study uses qualitative methods with primary data collected through interviews, in-depth group discussions, documentation, and observations. Data analysis uses frequency tables, percentage, and interpretation according to the theoretical framework. The results of the study show that the younger generation and university students have a positive attitude towards preventing the practice of money politics in the regional head election in Lampung. However, knowledge of prohibitions and sanctions for money politics needs to be further enhanced among them, both through political education and periodic active socialization by the election organizer (General Election Commission and Election Supervisory Agency), as well as through cooperation with higher education, group civil society groups, and schools.